Setting up the internal market in the banana sector (Commission of the European Communities BrusselsBE, 1992)
Analyses the situation on the Community market and the various constraints to be borne in mind. Studies the main ways and means of 'Communitising' the market, and sets out conclusions in line with the Commission's position. These conclusions are based on a ten-year scheme designed to enable producers and operators to adapt to the process of market decompartmentalisation.
DC